Label-free and sensitive MiRNA detection based on turn-on fluorescence of DNA-templated silver nanoclusters coupled with duplex-specific nuclease-assisted signal amplification - Ma, Gui-min; Huo, Li-wei; Tong, Yin-xia; Wang, Yu-cong; Li, Cui-ping; Jia, Hong-xia (Mikrochimica acta (1966), 2021)
A novel strategy for microRNAs (miRNAs) detection has been developed utilizing duplex-specific nuclease-assisted signal amplification (DSNSA) and guanine-rich DNA-enhanced fluorescence of DNA-templated silver nanoclusters (AgNCs). The combination between target miRNA, DSNSA, and AgNCs is achieved by the unique design of DNA sequences. Target miRNA opens the hairpin structure of the Hairpin DNA probe (HP) by hybridizing with the HP and initiates the duplex-specific nuclease-assisted signal amplification (DSNSA) reaction. The DSNSA reaction generates the release of the guanine-rich DNA sequence, which can turn on the fluorescence of the dark AgNCs by hybridizing with the DNA template of the dark AgNCs. The fluorescence intensity of AgNCs corresponds to the dosage of the target miRNA. This is measured at 630 nm by exciting at 560 nm. The constructed method exhibits a low detection limit (~8.3 fmol), a great dynamic range of more than three orders of magnitude, and excellent selectivity. Moreover, it has a good performance for miR-21 detection in complex biological samples. Graphical abstract A novel strategy for microRNAs (miRNAs) detection has been developed utilizing duplex-specific nuclease-assisted signal amplification (DSNSA) and guanine-rich DNA-enhanced fluorescence of DNA-templated silver nanoclusters (AgNCs).